The pornography use and its addiction among emerging adults in Malaysia: Perceived realism as a mediator. - Soon Aun Tan; Samantha Hui Li Ng; Juliana Ju Yun Hoo; Su Wan Gan; Sarvarubini Nainee; Chin Choo Yap; Ling Khai Lee; Norzarina Mohd Zaharim; Yee Shan Goh (PLoS ONE)
Past studies have demonstrated a link between pornography use and addiction to pornography, the underlying mechanism of the association is still unclear. This study intended to examine the mediating role of perceived realism of pornography in the association between pornography use and addiction among emerging adults in Malaysia. This study recruited 222 self-identified pornography users (M age = 21.05; SD Age = 1.68; 75.1% male respondents) via the purposive sampling method. The correlation results indicated positive associations among pornography use, addiction to pornography, and perceived realism of pornography. Further, the perceived realism of pornography significantly mediated the association between pornography use and addiction to pornography after controlling for gender. Thus, this study has provided a fundamental understanding on the perceived realism role of pornography in explaining the association between its use and addiction. Although it is unlikely to stop illegal pornography use, the results pointed out a need to guide emerging adults in pornography use via media literacy programmes.